BRCA1/2 Variant Data-Sharing Practices. Issue 1 (March 2019) - Bollinger, Juli M.; Sanka, Abhi; Dolman, Lena; Liao, Rachel G.; Cook-Deegan, Robert
Accessing BRCA1/2 data facilitates the detection of disease-associated variants, which is critical to informing clinical management of risks. BRCA1/2 data sharing is complex and many practices exist. We describe current BRCA1/2 data-sharing practices, in the United States and globally, and discuss obstacles and incentives to sharing, based on 28 interviews with personnel at U.S. and non-U.S. clinical laboratories and databases. Our examination of the BRCA1/2 data-sharing landscape demonstrates strong support for and robust sharing of BRCA1/2 data around the world, increasing global accesses to diverse data sets.